Forest Management in the Interface: Forest Health - Robert A. Schmidt (EDIS)
Revised! FOR-178, a 5-page illustrated fact sheet by Robert A. Schmidt, describes forest health concerns in the wildland-urban interface, which include slightly different issues and quite different management solutions than the same concerns in rural forests. Published by the UF School of Forest Resources and Conservation, July 2008.